Berberine Attenuates Cell Motility via Inhibiting Inflammation-Mediated Lysyl Hydroxylase-2 and Glycolysis - Du, Yishan; Khan, Muhammad; Fang, Nana; Ma, Fang; Du, Hongzhi; Tan, Zhenya; Wang, Hua; Yin, Shi; Wei, Xiaohui (Frontiers in Pharmacology, 2022)
Lysyl hydroxylase-2 (LH2) involves in the hydroxylation of telopeptide lysine residues during collagen deposition. Recent studies indicate that interleukin (IL)-6 generated by the chronic inflammation disease may trigger the LH2 expression to accelerate cell motility. Berberine is the alkaloid derived from the traditional Chinese medicine Coptis chinensis, which displays potential anti-inflammatory activity in multiple diseases. The anti-inflammatory activity of berberine has been confirmed by reducing proinflammatory cytokines such as IL-6, IL-8, and IFN-γ. However, whether and how berberine inhibits cellular motility against metastatic spread in triple-negative breast cancer (TNBC) has not been demonstrated, and the underlying mechanism remains unclear. We investigated the effects of berberine on the inflammatory cytokine secretion, cell proliferation, and migration in vitro and further explored the effect of berberine on growth and metastasis in vivo. Berberine restrained TNBC cell proliferation, motility, and glycolysis process in a dose-dependent way. The secretion of IL-6 was abrogated by berberine in TNBC cells, and IL-6-stimulated cell migration was inhibited by berberine. Mechanistically, berberine remarkably suppressed LH2 expression at both mRNA and protein levels. LH2 depletion led to decreasing the antimotility effect of berberine, and this phenomenon was related to the suppressed glycolysis after LH2 inhibition. Conversely, ectopic restoration of LH2 could further increase the antimotility effect of berberine. Moreover, berberine was confirmed to inhibit cell growth and motility in vivo, and the expression of LH2 and glycolytic enzymes was also blocked by berberine in vivo. Collectively, this study indicated that berberine could be a promising therapeutic drug via regulating LH2 for TNBC.